Recuay Tradition Sculptures of Chinchawas, North Highlands of Ancash, Peru - Lau, George F. (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
Recuay stone sculpture has been known to Western scholarship since the late 19th century. Together with their finely crafted pottery, stone sculpture marks groups of the Recuay cultural tradition, which developed in Northern Peruca. AD 1–700. The best-known monoliths portray figures of humans and felines. Although these subjects are not unfamiliar in world cultures, the highly stylized works do not readily resonate with traditional Western expectations of sculptural vérité or “objets d’art”. No clear stylistic predecessors exist for the Recuay tradition, nor were there clear successors. For over a century, the sculptures have been the subject for varied interpretations and iconographic comparisons. Unfortunately, there has been no systematic attempt to understand these ancient Andean artworks in context.The article will be available as a PDF in the near future.